Personality profiles, impact drug, and follow-up of patients treated in a rehabilitation center in Northeast Mexico - Reyes, Daniela; Andaverde Vega, Adrián Alberto; Ybarra Sagarduy, José Luis; Orozco Ramírez, Luz Adriana (Acta Universitaria, 2022)
The objective of this study was to explore the association between personality profile, impact drug, and discharge status in patients with substance use disorders. Desertion of addiction treatment is high; therefore, it is necessary to monitor it to know its causes. A total of 300 clinical records of patients admitted to a rehabilitation center were reviewed. A database containing variables of interest was prepared from the evaluation questionnaire of sociodemographic, psychological, and health variables. For the analysis, the correspondence analysis procedure was used. Among the main findings, it was found that the schizoid profile presented a higher frequency of alcohol consumption, while the antisocial and schizotypal profile increased frequency of marijuana use. Six months after discharge, patients with a paranoid and narcissistic profile had a higher frequency of abstinence.